(untitled) (Web of Teachers: Inderscience Research, 2025)
The liver plays a crucial role in metabolism, detoxification, and immune regulation. Disruptions in its physiological functions lead to a spectrum of liver diseases, including hepatitis, fatty liver disease, cirrhosis, and hepatocellular carcinoma. This article reviews the physiology and pathophysiology of the liver, highlighting current treatment modalities used in clinical practice.